No-fragile H∞ guaranteed cost control design for spacecraft rendezvous. Issue 28 (2015) - Xiangyu, Gao; Xian, Zhang; Julong, Tan; Jiaojiao, Li
Abstract: In this paper, the robust no-fragile H∞guaranteed cost control problem is considered for spacecraft orbit rendezvous. By using Lyapunov stability theory and linear matrix inequality(LMI) technique, a sufficient condition is derived for H∞ guaranteed cost control design of spacecraft orbit rendezvous, which is in the form of LMIs. The upper bound of the control constraint and H∞ performance index are both taken into consideration, giving rise to a new mixed performance index. Thus, a convex optimization problem with LMI constraints is obtained. The robust optimal no-fragile H∞ guaranteed cost controller can be given via solving this constrained convex optimization problem. With this optimal controller, the spacecraft rendezvous mission can be accomplished successfully in the presence of external disturbances. Numerical examples are given to demonstrate the effectiveness of the control design method proposed.